2020
DOI: 10.1186/s13613-020-00735-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic assessment of parasternal intercostal muscles during mechanical ventilation

Abstract: Although mechanical ventilation is a lifesaving treatment, abundant evidence indicates that its prolonged use (1 week or more) promotes respiratory muscle weakness due to both contractile dysfunction and atrophy. Along with the diaphragm, the intercostal muscles are one of the most important groups of respiratory muscles. In recent years, muscular ultrasound has become a useful bedside tool for the clinician to identify patients with respiratory muscle dysfunction related to critical illness and/or invasive me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 55 publications
(91 reference statements)
0
28
0
Order By: Relevance
“…The characteristics of the patients are shown in Table 1 (IQR, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The HFNC duration was 2 days (IQR, 2-3 days), which was due to post-extubation (29 patients, 73%) and respiratory failure types I (10 patients, 25%) and II (1 patient, 3%).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the patients are shown in Table 1 (IQR, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The HFNC duration was 2 days (IQR, 2-3 days), which was due to post-extubation (29 patients, 73%) and respiratory failure types I (10 patients, 25%) and II (1 patient, 3%).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the diaphragm muscle, intercostal muscle atrophy is also observed in patients with mechanical ventilation [ 62 ], and is associated with prolonged mechanical ventilation and prolonged ICU stay [ 42 ]. Moreover, muscle atrophy occurs in other expiratory muscles, including the obliquus interna, obliquus externa, transversus abdominis, and rectus abdominis muscles [ 63 ].…”
Section: Muscle Atrophymentioning
confidence: 99%
“…The matrigel medium was prepared and kept at 4℃. After the cell number was determined, the diaphragm satellite cells were seeded into 12-well plates at a density of 1.5×10 4 per well with 400 μL medium. The cells were cultured at 37 ℃ for 4 days.…”
Section: Cell Culture and View Divisionmentioning
confidence: 99%
“…Moreover, weaning failure is associated with increased morbidity and mortality, exposing patients to life-threatening complications again [3]. Accumulating evidence has indicated that the prolonged MV (1 week or longer) promotes respiratory muscle weakness due to both contractile dysfunction and atrophy, especially in the diaphragm [4][5][6][7], indicating that diaphragm dysfunction plays a key role in weaning failure from MV. Petrof BJ and Vassilakopoulo have termed such a condition as ventilatorinduced diaphragmatic dysfunction (VIDD) [8,9].…”
Section: Introductionmentioning
confidence: 99%